Unraveling the Pathways: A Meta-Analysis Exploring the Biopsychosocial Mechanisms Linking Psychosomatic Symptoms and Systemic Lupus Erythematosus - Ridho Pratama; Arina Widya Murni (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease characterized by a complex interplay of biological, psychological, and social factors. Psychosomatic symptoms, such as depression, anxiety, and stress, are common in individuals with SLE and can significantly impact disease activity and overall well-being. This meta-analysis aims to explore the biopsychosocial mechanisms linking psychosomatic symptoms and SLE. Methods: A systematic search of PubMed, Embase, PsycINFO, and Web of Science databases was conducted from January 2013 to December 2024. Studies examining the relationship between psychosomatic symptoms and SLE were included. Data were extracted and analyzed using random-effects models to calculate pooled effect sizes. Results: Six studies met the inclusion criteria. The meta-analysis revealed a significant association between psychosomatic symptoms (depression, anxiety, and stress) and SLE disease activity (pooled effect size: r = 0.42, 95% CI: 0.31-0.53, p < 0.001). Furthermore, dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis, pro-inflammatory cytokine activity, and impaired coping mechanisms emerged as key biopsychosocial pathways linking these factors. Conclusion: This meta-analysis highlights the significant impact of psychosomatic symptoms on SLE and identifies potential underlying mechanisms. These findings underscore the need for integrated biopsychosocial interventions in SLE management, targeting both physical and psychological well-being to improve patient outcomes.